"Na Antenie" and "Wiadomości": the Circumstances of the Beginnings and Termination of Cooperation - Moczkodan, Rafał (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2024)
English version. Original issue: “Archiwum Emigracji” 2015, no. 1–2 (22–23) https://apcz.umk.pl/AE/article/view/AE.2015.005